Climate change and agricultural development - Rosegrant, Mark W.; Wiebe, Keith D.; Sulser, Timothy B.; Mason-D’Croz, Daniel; Willenbockel, Dirk (International Food Policy Research Institute, 2021)
Climate change will be a major driver of change in the agricultural sector in the coming decades, along with changes in population, income, urbanization, dietary preferences, and technology.1 Agriculture is unique among economic sectors in its dependence on temperature, precipitation, and other climate variables, and is thus unique in its sensitivity to changes in those variables. Farmers around the world have long been accustomed to dealing with the vagaries of weather, but climate change is now occurring on a larger scale and will bring bigger challenges in terms of what farmers produce, where and how they produce it, and what we eat.